Flexible electrogenerated electrostatic adsorption material, preparation method and application of flexible electrogenerated electrostatic adsorption material in preparation of flexible grabbing actuator
By using flexible electrostatic adsorption materials containing MOF and thermoplastic elastomers, the problems of high driving voltage and low adsorption force in the prior art are solved, and materials with high electrostatic adsorption force at lower voltages are realized, and materials with wide application in Flexible grippers and wearable gloves and other fields.
Patent Information
- Application Number
- CN202411634496.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-07
AI Technical Summary
The existing flexible electrostatic adsorption materials with single electrodes have problems such as high driving voltage and low electrostatic adsorption force, which limits their application.
Materials of different shapes are obtained by using flexible electrostatic adsorption materials containing metal organic framework compounds (MOFs) and thermoplastic elastomers, and materials of different shapes are obtained by solution processing or melt processing, and are used to prepare flexible actuators.
It exhibits a large electrostatic adsorption force at lower voltages and has a wide range of applications. It can form a flexible grasper from a single or multiple actuators to achieve the grasping and variable stiffness of objects in different shapes under different electric fields.
Smart Images

Figure CN119391166A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible electrostatic adsorption materials and flexible actuators, and in particular relates to a flexible electrostatic adsorption material and its application in flexible grasping actuators and electroadhesion-assisted wearable gloves. Background Art
[0002] Electrostatic adsorption materials are a type of material that can produce electrostatic adsorption under the action of an electric field. Electrostatic adsorption materials can be used in air purification, adsorption and fixation related components in medical devices, and gripping. Flexible electrostatic adsorption materials are generally composed of electrodes and flexible dielectric materials. One type is an electrostatic adsorption material for interdigital electrodes, which requires a higher dielectric constant; the other is an electrostatic adsorption material for a single electrode. The patent application with application number 202410387033.X in the prior art discloses a single-electrode flexible electrostatic adsorption material with the characteristics of simple preparation process and excellent performance, and has important applications in intelligent devices such as clutches, flexible grippers, bionic wings and lifters. However, the current single-electrode flexible electrostatic adsorption materials have problems such as high driving voltage and low electrostatic adsorption force, which limit their application. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, in order to solve the problem that the single-electrode flexible electrostatic adsorption material has a high driving voltage and a low electrostatic adsorption force, the purpose of the present invention is to design and provide a flexible electrostatic adsorption material, a preparation method and its application in the preparation of an actuator. The electrostatic adsorption peel strength of the flexible electrostatic adsorption material of the present invention at 1kV reaches 1085mN / cm 2 , can be applied to intelligent devices such as clutches and flexible grippers in the fields of flexible robots, health care and wearable devices.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] On the one hand, the present invention provides a flexible electrostatic adsorption material, which comprises the following raw materials in parts by weight: 0.3 to 1.5 parts of a metal organic framework compound (MOF) and 100 parts of a thermoplastic elastomer.
[0006] The flexible electrostatic adsorption material, wherein the thermoplastic elastomer is at least one of thermoplastic polyurethane elastomer (TPU), styrene-ethylene-butylene-styrene block copolymer (SEBS), maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer or styrene-butylene-styrene block copolymer (SBS).
[0007] The flexible electrostatic adsorption material, wherein the MOF is at least one of the ZIF series or the UiO-66 series;
[0008] Preferably, the ZIF series is ZIF-8.
[0009] In a second aspect, the present invention provides a method for preparing a flexible electrostatic adsorption material as described in any one of the above, comprising the following steps:
[0010] (1) weighing a metal organic framework compound and dissolving it in a solvent, mixing the mixture evenly, adding the metal organic framework compound and mixing the mixture evenly to obtain a polymer solution;
[0011] (2) Casting or coating the polymer solution, and drying it to obtain a thermoplastic elastomer / metal organic framework compound composite film.
[0012] The preparation method, wherein the solvent is dimethylformamide;
[0013] The thickness of the thermoplastic elastomer / metal organic framework compound composite film is 40-100 μm.
[0014] In a third aspect, the present invention provides a flexible actuator, comprising a flexible electrode, and any one of the flexible electrostatic adsorption materials coated on the upper and lower surfaces of the flexible electrode, respectively.
[0015] In the flexible actuator, the raw materials of the flexible electrode include conductive filler and aqueous polyurethane solution;
[0016] Preferably, the thickness of the flexible electrode is 5-10 μm.
[0017] In the flexible actuator, the conductive filler is at least one of carbon black and carbon nanotubes;
[0018] The waterborne polyurethane is at least one of the waterborne polyurethane series;
[0019] The mass ratio of the conductive filler to the waterborne polyurethane is 0.8-1.5:1.
[0020] The solid content of the waterborne polyurethane is 35wt.% to 45wt.%.
[0021] A flexible gripper, comprising any one of the following combinations:
[0022] (1) A flexible electrostatic adsorption material actuator, and connecting a positive electrode and an electrode; in method (1), after one of the flexible actuators is connected to the positive electrode, the electric adhesion force between the flexible electrostatic adsorption material actuator and other objects can be controlled by voltage; the voltage of the positive electrode is determined by the required electric adhesion force, and in some specific embodiments can be set to 0.4 to 2 kV.
[0023] (2) Two flexible electrostatic adsorption material actuators, each connected to a positive electrode and a negative electrode; in the technical solution of the present invention, in method (2), in some specific embodiments, it can be used as a gripper to grab objects of different sizes, and the voltage difference between the positive electrode and the negative electrode is 0.4-2kV.
[0024] (3) Two or more flexible electrostatic adsorption material actuators connected with a negative electrode and multiple positive electrodes.
[0025] Application of the flexible electrostatic adsorption material in the preparation of intelligent devices;
[0026] Preferably, the intelligent device is a flexible actuator, a clutch, a flexible gripper, a bionic wing or a jack.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The flexible electrostatic adsorption material of the present invention is obtained by solution processing or melt processing to obtain materials of different shapes, and does not require a curing process, and the structure and preparation method of the flexible electrostatic adsorption material actuator are simple. The flexible electrostatic adsorption material of the present invention exhibits a large electrostatic adsorption force at a relatively low voltage, and has a wide range of applications. A flexible gripper can be composed of a single or multiple actuators to achieve the gripping of objects of different shapes and variable stiffness under different electric fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The XRD and AFM images of the TPU / ZIF-8 composite film prepared in Example 1, wherein a is the XRD image of the TPU / ZIF-8 composite film, and b is the AFM image of the TPU / ZIF-8 composite film;
[0030] Figure 2 The present invention is a method for testing the peeling strength of a flexible actuator made of an electrostatic adsorption material, wherein a is a schematic diagram of testing the peeling strength of a flexible actuator made of an electrostatic adsorption material, and a physical diagram of testing the peeling strength of a flexible actuator made of an electrostatic adsorption material;
[0031] Figure 3 This is a graph showing the peel strength test results of the electrostatic adsorption material flexible actuator prepared in Examples 2-7 of the present invention;
[0032] Figure 4 This is a diagram showing an example of the use of the flexible gripper prepared in Example 8 of the present invention;
[0033] Figure 5 It is an electroadhesion-assisted wearable glove, where a is a real picture of the electroadhesion-assisted wearable glove, and b is a real picture of the electroadhesion-assisted wearable glove grasping an object. DETAILED DESCRIPTION
[0034] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0035] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art. In the following embodiments, thermoplastic polyurethane (TPU) was purchased from BASF's 1180A brand, and zeolite imidazole framework material (ZIF-8) was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0036] Embodiment 1:
[0037] A method for preparing a flexible electrostatic adsorption material comprises the following steps:
[0038] (1) 0.014 g ZIF-8 and 20 mL dimethylformamide (DMF) were mixed and mechanically stirred for 4 h to obtain a solution;
[0039] (2) adding 2 g of TPU to the solution obtained in step (1), and mechanically stirring for 4 h to mix the mixture evenly to obtain a polymer solution;
[0040] (3) The polymer solution obtained in step (2) is coated on a glass plate as a carrier on a coating machine at 70° C. The coating height is set to 3 mm. After coating, the coating is allowed to stand for 30 minutes, and the glass plate is placed in an oven at 80° C. for 2 hours;
[0041] (4) The film was cooled to room temperature and then placed in an oven at 80°C for annealing for 8 h to obtain a TPU / ZIF-8 composite film with a thickness of 60 μm. Figure 1 Figure 2 shows the XRD and AFM images of the TPU / ZIF-8 composite film. It can be seen that ZIF-8 is uniformly dispersed in TPU.
[0042] Embodiment 2:
[0043] A method for preparing a flexible actuator using a flexible electrostatic adsorption material comprises the following steps:
[0044] (1) 0.06 g of carbon black was mixed with 0.04 g of an aqueous polyurethane solution having a solid content of 35 wt %, dissolved in 40 mL of isopropanol, stirred evenly with a glass rod, and then ultrasonically dispersed at room temperature for 1 hour to prepare a conductive slurry.
[0045] (2) The conductive slurry is injected into a sprayer and sprayed onto the TPU / ZIF-8 composite film. The amount of spraying is determined by the electrode area to be sprayed. In this embodiment, it is 7 g / dm 2 The sprayed TPU / ZIF-8 composite film was placed in a vacuum oven at 50°C for 40 minutes to evaporate the solvent, so that a flexible electrode was sprayed on the TPU / ZIF-8 composite film.
[0046] (3) Dissolve 0.15 g of an aqueous polyurethane solution with a solid content of 35% in 40 mL of isopropanol, stir evenly with a glass rod, and then ultrasonically disperse at room temperature for 1 hour to prepare a WPU solution. Then inject the WPU solution into a sprayer and spray it on the flexible electrode of the TPU / ZIF-8 composite film obtained in step (2) to encapsulate the surface of the flexible electrode; after spraying, place it in a vacuum oven at 50°C for 40 minutes to volatilize the solvent.
[0047] (4) Hot pressing the TPU / ZIF-8 composite film with the sprayed flexible electrode obtained in steps (2) and (3) and the TPU / ZIF-8 composite film without the sprayed flexible electrode to obtain an electrostatic adsorption material flexible actuator. The sprayed surface of the TPU / ZIF-8 composite film with the sprayed flexible electrode faces the TPU / ZIF-8 composite film without the sprayed flexible electrode; the temperature of the hot press is 120°C, and the hot pressing time is 5 minutes; during the hot pressing process, the vacuum time is 1 minute, and the pressure of the vacuum hot pressing is 0.65MPa.
[0048] Embodiment 3:
[0049] In this embodiment, the preparation process of the electrostatic adsorption material flexible actuator is the same as that of Embodiments 1 and 2, except that in step (1) and step (2) of Embodiment 1, the mass of ZIF-8 is 0 g, and TPU and DMF are directly mixed and stirred.
[0050] Embodiment 4:
[0051] In this embodiment, the preparation process of the electrostatic adsorption material flexible actuator is the same as that of Embodiments 1 and 2, except that in step (1) of Embodiment 1, the mass of ZIF-8 is 0.006 g.
[0052] Embodiment 5:
[0053] In this embodiment, the preparation process of the electrostatic adsorption material flexible actuator is the same as that of Embodiments 1 and 2, except that in step (1) of Embodiment 1, the mass of ZIF-8 is 0.01 g.
[0054] Embodiment 6:
[0055] In this embodiment, the preparation process of the electrostatic adsorption material flexible actuator is the same as that of Embodiments 1 and 2, except that in step (1) of Embodiment 1, the mass of ZIF-8 is 0.02 g.
[0056] Embodiment 7:
[0057] In this embodiment, the preparation process of the electrostatic adsorption material flexible actuator is the same as that of Embodiments 1 and 2, except that in step (1), the mass of ZIF-8 is 0.03 g.
[0058] Performance Testing:
[0059] The peel strength of the electrostatic adsorption material flexible actuator prepared in Examples 2-7 was tested, and the test method was as follows:
[0060] A4 paper is pasted on the surface of the fixed plate, and one end of the fixed plate is fixed, and the paper is regarded as the adhered object; one end of the electrostatic adsorption material flexible actuator is fixedly connected to the load sensor, and the other end is hung close to the A4 paper pasted on the fixed plate; after the electrostatic adsorption material flexible actuator is powered on, it will be adsorbed on the A4 paper due to the electric adhesion force; during the vertical upward stretching process, the peeling strength is obtained through the load sensor, such as Figure 2 shown.
[0061] The test results of the electrostatic adsorption material flexible actuator prepared in Examples 2-7 at different voltages are shown in Figure 3 , it can be seen from the figure: the amount of ZIF-8 raw material added in Examples 2-7 is different. Under the same voltage, the peel strength changes significantly with the increase of ZIF-8 content; before the content is 0.7 parts, the peel strength increases significantly with the increase of content. After the ZIF-8 content is 0.7 parts, the peel strength decreases with the increase of content. However, under the same voltage, the electrical adhesion peeling strength of the TPU / ZIF-8 composite thin film flexible actuator with added ZIF-8 is much greater than that of the TPU thin film flexible actuator without added ZIF-8.
[0062] Embodiment 8:
[0063] A flexible gripper: A flexible gripper is formed by two actuators prepared in Example 2. One of them is connected to the negative electrode and the other is connected to the positive electrode. The voltage given is 1kV. The flexible gripper can grasp an object of 539g. Figure 4 As shown, the feasibility of applying the flexible electrostatic adsorption material actuator of the present invention in a flexible gripper is demonstrated.
[0064] Embodiment 9:
[0065] An electroadhesion-assisted wearable glove: The actuators prepared by two embodiments 2 are attached to the finger parts of the glove. The prosthesis wears the glove with electroadhesion, connects to the positive electrode, and can grasp the real object under the voltage of 1kV; Figure 5 As shown, it is proved that the flexible electrostatic adsorption material actuator of the present invention is applied to wearable gloves, which can effectively contact and grasp objects. The electroadhesion-assisted wearable gloves can help patients with myasthenia gravis, rheumatoid bone disease and other grasping difficulties to overcome grasping obstacles, providing feasibility.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A flexible electrostatic adsorption material, characterized in that: The flexible electrostatic adsorption material comprises the following raw materials in parts by weight: 0.3 to 1.5 parts of a metal organic framework compound and 100 parts of a thermoplastic elastomer.
2. A flexible electrostatic adsorption material as claimed in claim 1, characterized in that: The thermoplastic elastomer is at least one of thermoplastic polyurethane elastomer, styrene-ethylene-butylene-styrene block copolymer, maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer or styrene-butylene-styrene block copolymer.
3. A flexible electrostatic adsorption material as claimed in claim 1, characterized in that: The metal organic framework compound is at least one of a ZIF series or a UiO-66 series metal organic framework compound; Preferably, the ZIF-based metal organic framework compound is ZIF-8.
4. A method for preparing a flexible electrostatic adsorption material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) weighing a metal organic framework compound and dissolving it in a solvent, mixing it uniformly, adding the metal organic framework compound, mixing it uniformly, and obtaining a polymer solution; (2) Casting or coating the polymer solution, and drying it to obtain a thermoplastic elastomer / metal organic framework compound composite film.
5. The preparation method according to claim 4, characterized in that: The solvent is dimethylformamide; The thickness of the thermoplastic elastomer / metal organic framework compound composite film is 40-100 μm.
6. A flexible actuator, characterized in that: It comprises a flexible electrode, and the flexible electrostatic adsorption material as claimed in any one of claims 1 to 3 coated on the upper and lower surfaces of the flexible electrode respectively.
7. A flexible actuator as claimed in claim 6, characterized in that: The raw materials of the flexible electrode include conductive filler and aqueous polyurethane solution; Preferably, the thickness of the flexible electrode is 5-10 μm.
8. A flexible actuator as claimed in claim 7, characterized in that: The conductive filler is at least one of carbon black or carbon nanotubes; The waterborne polyurethane is at least one of the waterborne polyurethane series; The mass ratio of the conductive filler to the waterborne polyurethane is 0.8 to 1.5:1; The solid content of the waterborne polyurethane is 35wt.% to 45wt.%.
9. A flexible gripper, characterized in that: Contains any of the following combinations: (1) a flexible electrostatic adsorption material actuator connected to the positive electrode and the electrode; (2) two flexible electrostatic adsorption material actuators, each connected to a positive electrode and a negative electrode; (3) Two or more flexible electrostatic adsorption material actuators connected with a negative electrode and multiple positive electrodes.
10. Use of the flexible electrostatic adsorption material according to any one of claims 1 to 3 in the preparation of smart devices; Preferably, the intelligent device is a flexible actuator, an electroadhesion-assisted wearable glove, a clutch, a flexible gripper, a bionic wing or a lifter.
Citation Information
Patent Citations
Elastomer actuator and preparation method, application and driving method thereof
CN118284306A